Reparations for indigenous women subjected to sexual and environmental violence in the Colombian post-peace agreement - Loperena, Ana Iris (International journal of transitional justice, 2023)
The peace agreement with the Fuerzas Armadas Revolucionarias de Colombia involved both gender- and ethnic-based approaches. However, crimes against the sexual freedom and integrity of indigenous women and related territorial rights reparations continue to be problematic. Notably, no in-depth knowledge exists regarding the individual and collective effects of sexual and environmental violence on indigenous women, the obstacles hindering their access to ordinary justice, special indigenous jurisdiction or peace jurisdiction. Therefore, this study aims to analyse the conceptualizations of restorative justice and reparation from the perspective of indigenous Wiwa women. To do so, it focuses on the case of the Marokazo and Teyunke regions, examining some important characteristics of indigenous reparation processes vis-à-vis sexual and environmental violence against this community. It also explores the individual conditions underlying the development of local indigenous reparation processes and the place of biological materials and natural resources in these reparation processes.